The Political Communications of Khofifah Indar Parawansa to Obtain Support of the Golkar Party, the Democrat Party, and Nahdlatul Ulama Figures in the 2018 East Java Governor Election - Ahmad Tamrin Sikumbang; Syukur Kholil; Ramdeswati Pohan (Randwick International of Social Science Journal, 2021)
Identity politics is often seen as preventing a woman from becoming a leader. In fact, the potential for leadership is a gift from God that must be managed wisely, responsibly, and full of trust. In the Qur'an sura Al Baqarah verse 228 Allah SWT gives His signal that women have equal rights with men in all matters including leadership. Twice failed in the East Java Governor Election did not stop Khofifah Indar Parawansa's determination to return to participate in the for the third time. This study has the aim of knowing the political communication efforts carried out by Khofifah Indar Parawansa in gaining the support of the Golkar Political Party and the Democratic Party as well as NU figures so that they win the 2018 East Java Governor election. The research method used in this study is to use qualitative analysis with a phenomenological approach that uses a phenomenological approach. Relies on data collection, including interviewing key informants and several other key informants, as well as conducting in-depth analysis of a series of studies. The results of this study conclude that the political communication process of Khofifah Indar Parawansa before becoming the Governor of East Java for the 2018-2023 period, the main thing is to build intensive political communication to the Kiai Nahdlatul Ulama (NU) as informal figures who are influential in East Java. Through the role of the NU (Nahdliyin) East Java clerics, strategies and patterns of political communication were developed with local political figures from major political parties to win the 2018 East Java Governor election contestation.